2002
DOI: 10.2118/80146-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive, Practical Approach For Wellbore Instability Management

Abstract: In the northwest shelf, a region of growing importance for oil and gas production in Australia, drilling delays and well suspension before reaching targets have occurred frequently because of wellbore instability. As a result, the economic benefits from new drilling technologies are significantly reduced because of high additional drilling costs. To improve drilling efficiency and minimize drilling costs, it is crucial to develop and apply a practical approach for optimizing wellbore instability management.Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The anisotropic poroelastic models mainly embody the effect of rock poroelastic anisotropies on borehole stability; however, Aadnøy (1988) concluded rock anisotropic elasticity parameters had a minor influence on fracture pressure. Chen et al (2002) found the safe mud-weight window was not significantly affected by rock poroelastic anisotropies for most of the drilling formations encountered.…”
Section: Introductionmentioning
confidence: 87%
“…The anisotropic poroelastic models mainly embody the effect of rock poroelastic anisotropies on borehole stability; however, Aadnøy (1988) concluded rock anisotropic elasticity parameters had a minor influence on fracture pressure. Chen et al (2002) found the safe mud-weight window was not significantly affected by rock poroelastic anisotropies for most of the drilling formations encountered.…”
Section: Introductionmentioning
confidence: 87%
“…Para que exista estabilidad entre el hueco perforado y las rocas circundantes, debe predominar el equilibrio de todos los esfuerzos, es decir, que estos sean lo más parecidos posible. Para ello, deben controlarse la dirección del pozo y el peso del lodo [12]. La deficiencia en el control del peso del lodo puede generar problemas como colapsos (o comúnmente breakout) o fracturas [13].…”
Section: Estabilidad De Pozosunclassified
“…Although some researchers state that non-linear approaches can deliver more accurate results, they have acknowledged that some input parameters in such models are hardly available (Fleming et al, 1990;Woodland, 1990). On the other hand, Tan et al (1999) and Chen et al (2002) showed that in ordinary oil-filled wellbores, the minimum (critical) support pressure required to keep the wellbore stable is not significantly influenced by the elastic anisotropy. In this paper for a vertical borehole the stresses which were generated on an element at the borehole wall due to far field stresses were calculated based on the elastic theory.…”
Section: State Of Stress Around a Vertical Boreholementioning
confidence: 99%
“…The in situ stress state can be defined in terms of the principal stresses, σ v , σ H , and σ h . The ratio of minimum horizontal stress to the vertical stress (k o = σ h /σ v ) ranges from 0.3 to 1.5 and the ratio of maximum horizontal stress to minimum horizontal stress (σ H /σ h ) varies from 1 to 2 in most of oil fields and exploration boreholes (Herget, 1988;Tan et al, 1993;Chen et al, 2002). Based on the tectonic and faulting condition, Anderson (1951) suggested three different stress regimes for the underground stress conditions.…”
Section: Introductionmentioning
confidence: 99%